The Scope of nursing interventions in the care of patients in the perioperative period using the International Classification for Nursing Practice - Grabowska, Hanna; Grabowski, Władysław (Nursing Problems / Problemy Pielęgniarstwa, 2014)
ICNP® is an integral part of the global information infrastructure informing health care practice and policy to improve patient care worldwide. The aim of this work was an attempt to cross-map the terms describing the actions taken in the care of patients in the perioperative period with the interventions included in the ICNP catalogue. Based on a review of articles and academic textbooks published in Poland in the last decade, the most common actions that are important in the pre- and postoperative care of the patient have been selected. ICNP version 2013 enables describing nursing interventions implemented in the pre- and postoperative care.